Monumental Misunderstandings: The Material Entextualization of Mutual Incomprehension in Sino-Mozambican Relations. Issue 3 (1st September 2020) - Nielsen, Morten; Bunkenborg, Mikkel
Abstract: A statue of stainless steel cast in China and placed at the entrance of the new National Stadium in Mozambique sparked controversy between Chinese donors and Mozambican recipients in the period leading up to the stadium's 2011 inauguration. Based on ethnographic fieldwork among the Mozambican and Chinese nationals involved in the project, we explore the multiple misunderstandings surrounding the statue and show how they came to define Sino-Mozambican relations. Entextualized through materiality, the misunderstandings assumed a monumental form in the statue, and the message of mutual incomprehension continued to reverberate across the social terrain of Sino-Mozambican relations long after the statue itself had been removed. Misunderstandings, we argue, should not be dismissed as ephemeral communicative glitches, but seen as productive events that structure social relations.